2008
DOI: 10.1007/s00784-008-0240-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of Candida albicans hyphae and Lactobacillus in denture-related stomatitis

Abstract: Denture-related stomatitis (DRS) is still a dilemma in removable prosthodontics. The aim of this study was to investigate the relationship of DRS with the presence of Candida albicans hyphae and Lactobacillus. A total of 91 patients wearing maxillary and mandibular complete dentures were included in the present study and tested mycologically as well as bacteriologically. A statistically significant association of DRS was found with denture age (p = 0.003) and continuous denture wearing (p = 0.015). Presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 41 publications
3
51
0
9
Order By: Relevance
“…It includes local and systemic factors related to the host and to the Candida capability to adhere and proliferate in the host epithelial tissues (6). Candida-associated denture stomatitis is able to rise up when the conditions of the micro oral environment are favourable for the growth and the adhesion of the yeast and also when systemic factors of the host bring to a depression of the mechanisms of defence.…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…It includes local and systemic factors related to the host and to the Candida capability to adhere and proliferate in the host epithelial tissues (6). Candida-associated denture stomatitis is able to rise up when the conditions of the micro oral environment are favourable for the growth and the adhesion of the yeast and also when systemic factors of the host bring to a depression of the mechanisms of defence.…”
Section: Pathogenesismentioning
confidence: 99%
“…Candida, therefore, plays a key pathogenetic role in the onset of the denture stomatitis, even if the cooperative role practiced by the bacterial plaque present on the denture must not be neglected (12). Adhesion The ability of Candida to pass through the tissues is the first step of the infectious process (6,14). It has been observed that the forms endowed with hyphae are able to stick and to invade more quickly the tissues of the host.…”
Section: Permeability Of the Acrylic Resinsmentioning
confidence: 99%
“…Denture plaque derived from oral microorganisms adhering to the denture surface contains the fungus Candida albicans (C. albicans), which is known as one of the major causes of denture stomatitis [1][2][3] . Removal of this fungus may be effective for the treatment and prevention of denture stomatitis 4) .…”
Section: Introductionmentioning
confidence: 99%
“…Critical local risk factors are deficient oral hygiene, nighttime prosthesis wearing, old dentures, prosthesis instability, and traumatism [4][5][6][7][8][9][10][11]. Candida spp., a normal commensal microorganism in oral cavity, can be the pathogenic agent because of the ability to adhere and proliferate through the tissues of oral cavity [2,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Candida spp., a normal commensal microorganism in oral cavity, can be the pathogenic agent because of the ability to adhere and proliferate through the tissues of oral cavity [2,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%